HEALTH STATUS OF RURAL WOMEN AGRO-FOOD PROCESSORS IN ODOGBOLU LOCAL GOVERNMENT AREA OF OGUN STATE, NIGERIA - Aminu, F. O.; Balogun, E. O. S.; Falola, O. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2018)
Health promotes efficiency in production since it has direct effect on the producers, hence poor health impairs agricultural system. Poor health could lead to decreased working days, worker’s capacity, ability to explore diverse innovation and farming practices. This study was therefore carried out to assess the health status of rural women agro-food processors in Odogbolu Local Government Area, Ogun state, Nigeria. A survey research method was employed for the study and primary data were collected from one hundred and twenty respondents (120) through the use of a interview scheduled using multistage sampling techniques. Descriptive statistics and logit regression model were used for the study analysis. The results of the study revealed that most (83.5%) of the women were involved in more than one processing activities in the study area. A vast majority (91.67%) of the respondents experienced back pain while 87.5 percent reported headache as their common health problem. The result also revealed that self-medication was the highest mode of treatment due to distance to health facility centres. Findings from the logit regression analysis revealed that age (p<0.05), education (p<0.05), time spent (p<0.01), training (p<0.01) and wearing of protective garments (p<0.01) were the significant determinants of health status of the women processors in the study area. The study therefore concluded and recommended that women agro-food processors should be trained to become aware of the implication of processing activities on their health. There is need for government to make health care affordable and be within the reach of the farming community.